Fetuin A and fetuin B as an indicator of liver fibrosis in hepatitis B - Senol, Arzu; Balin, Safak Ozer; Toraman, Zuelal Asci (Walter de Gruyter Gmbh, 2024)
Objectives The aim of this study is to investigate the diagnostic and prognostic characteristics of fetuin A and fetuin B in chronic hepatitis B(CHB) and HBe Ag-negative chronic infection (HCI) and the relationship between the levels of these proteins and fibrosis in CHB.Methods In this study, we examined 98 patients with CHB, 58 with HCI and 42 control groups. Fetuin A and B levels were determined via ELISA.Results Serum fetuin A and B levels were significantly higher in the control group than the hepatitis B cases (p=0.001). No significant difference in fetuin A and B levels between patients in the CHB and HCI. In the CHB, fetuin A level was significantly lower in patients with significant fibrosis than those with mild fibrosis (p=0.007). Fetuin B was lower in patients with significant fibrosis than in with mild fibrosis; however, this difference was not significant. In predicting the absence of significant fibrosis, the area under the curve was estimated as 0.855 for fetuin A and 0.866 for fetuin B using the ROC curve.Conclusions Fetuin A and B were lower in CHB and HCI compared to the control group and there was no difference between the two groups suggests that these proteins may be effective in the pathogenesis of hepatitis B-induced liver damage. Fetuin A and B, which are found to be lower in patients with significant fibrosis in CHB, can be used as non-invasive markers in the early detection of fibrosis and in the follow-up of progression to significant fibrosis.
Keywords: hepatitis B; fibrosis; fetuin A; fetuin B; ELISA